The Hegemonic Character of Techno-Functional Neo-Immanentism and Its Relationship with Culture Wars - Celso Sánchez Capdequí; Javier Gil-Gimeno; Pablo Echeverría Esparza (Religions, 2023)
This paper analyzes the social processes that have led to the consolidation of a technocratic secular order and the type of cultural struggle that has made this possible. To this end, it first proposes a reconstruction of the technocratic consciousness in the course of the secularization process that culminates in the technological determinism or technological solutionism of the social present; then, the analysis focuses on the neo-immanentist tendency of techno-functionalism, in which the secular context and the text of secularization become one and deplete a social explanation; thirdly, it reflects on and deals with the open nature of secular life, in which context does not determine social texts (inter-actions) and opens the way to the existence of different life options that compete with each other and even turn on—rebel against—institutional design. This reflection, then, focuses on the specific features of the culture wars in Western Judeo-Christian culture and its globalizing tendency. Finally, the document closes with a conclusion that analyzes the road travelled and introduces the new challenges arising from the arguments presented.